EXAMINING THE INFLUENCE OF STORE LAYOUT ON CUSTOMER DECISIONS IN THE CAFÉ INDUSTRY - Eisya Sabilatul Fitroh; Zahra Allya Dika; Alya Fitria Sari; Ela Nurlaela (International Journal of Economics, Education, Law and Social Sciences (IJEELSC), 2026)
This study analyzes the influence of business space layout on customer decisions at Café Kosan Mantan, Tangerang City, which is one of the popular hangout destinations in the urban area. Using an explanatory survey quantitative approach, primary data was collected from customer respondents through a Likert scale-based questionnaire that had undergone validity and reliability tests, then analyzed by multiple linear regression using SPSS software. The results of the analysis show that there is a significant influence of the ergonomic arrangement of the space such as ease of access, movement paths, arrangement of furniture, and the interaction of physical elements on the decision of customers to visit, buy again, and give recommendations to others. The characteristics of respondents were dominated by young students with the frequency of regular visits for hangout, relaxation, or study activities, which further emphasized the crucial role of spatial layout in shaping urban consumer behavior and loyalty amid fierce competition in the café industry. This study recommends the optimization of business space design in a sustainable manner to strengthen customer retention, accompanied by follow-up study suggestions that integrate supporting variables such as digital factors and additional services cape.